Sustainable urban mobility in Rio de Janeiro: A model to quantify greenhouse gas emissions and purpose of practical application - Oliveira, Camila de Mello Cardoso de; Wolff, Mariana Gonçalves de Carvalho (Brazilian Journal of Operations & Production Management, 2020)
Goal: This article aims to present a mathematical modelling study to quantify greenhouse gas emissions in the scope of urban mobility and propose actions for more sustainable cities. Methodology: This presents an application focused on trips made by cars and motorcycles in some neighborhoods of the City of Rio de Janeiro during 2016 in order to quantify from mathematical equations the greenhouse gas emissions and their proportion to the total greenhouse gases emission of transport in the city, while presenting the capacity of the current bicycle infrastructure to absorb the same displacements with zero carbon trips. Results: The study reached the result of 127 thousand tons of greenhouse gases emitted by cars and motorcycles, representing 1,64% of the total transport emissions and 2,73% of road transport in this city in 2016. Limitations of the investigation: The research is limited to the neighborhoods under analysis and the daily travel rate per inhabitant by type of transport. Practical implications: The study provides environmental impact assessment material able to support proposals for practical applications aimed at mitigating greenhouse gas emissions. Originality/Value: Measurement of environmental impacts and applications in the transport of the city of Rio de Janeiro, which can be used for comparisons with other neighborhoods in the city and/or other cities.